Programmed Cell Death of Endothelial Cells in Myocardial Infarction and Its Potential Therapeutic Strategy - Mingyue Wu; Zixia Huang; Lijin Zeng; Chunfei Wang; Deming Wang (Cardiology Research and Practice)
Cardiovascular disease, especially coronary artery disease and stroke, kills around one-third of the world’s population, and myocardial infarction, a primary symptom of coronary heart disease, is a major worldwide health problem. Cardiovascular disease research has historically focused on promoting angiogenesis following myocardial damage. Myocardial vascular repair is crucial for improving myocardial infarction prognosis. Endothelial cells, the largest population of nonmyocytes within myocardial tissue, play an important role in angiogenesis. In recent years, different types of programmed cell death such as apoptosis, necroptosis, pyroptosis, ferroptosis, and autophagy have been described and found to be linked with cardiovascular diseases such as myocardial infarction, heart failure, and myocarditis. This will have important implications for reforming the treatment strategy of cardiovascular diseases. Different types of cell death of endothelial cells in myocardial infarction have been proposed, the roles and mechanisms of endothelial cell death in myocardial infarction are summarized in this review, and endothelial cell death inhibition as a therapeutic technique for treating myocardial infarction might be advantageous to human health.